Evaluation of the shared decision-making process scale in cancer screening and medication decisions. (March 2023) - Vo, Ha; Valentine, K.D.; Barry, Michael J.; Sepucha, Karen R.
Abstract: Objectives: Examine reliability and validity of the Shared Decision-Making (SDM) Process scale for cancer screening and medication decisions. Methods: Secondary data analysis from 6174 participants who made decisions about cancer screening (breast, colon or prostate) or medication (menopause, depression, hypertension or high cholesterol). Key measures included the SDM Process scale, decisional conflict, decision regret, and decision quality. Construct validity was examined by testing whether higher SDM Process scores were associated with lower regret, lower decisional conflict and higher decision quality. Meta-analyses summarized data across studies. Some studies assessed the scale's reliability. Results: Average SDM Process scores ranged from 1.2 to 2.5. There was a moderate-to-large, positive association between scores and lack of decisional conflict (cancer screening: d=0.61, CI(0.38, 0.84), p < .001; medications: d=0.36, CI(0.29, 0.44), p < .001). High scores were associated with lower decision regret (cancer screening: d=−0.24, CI(−0.37, −0.11), p < .001; medications: d=−0.30, CI(−0.40, −0.20), p < .001). There was no relationship with decision quality. Retest reliability was acceptable (ICC>0.7) for seven of eight clinical samples. Conclusions: The SDM Process scale demonstrated construct validity and retest reliability in cancer screening and medication decisions. Practice implications: The validated SDM Process scale is a short, patient reported metric to evaluate the current state of SDM. Highlights: The Shared Decision Making Process scale is a 4-item, patient-reported measure. Meta analysis shows evidence of validity and reliability in nonsurgical decisions. No ceiling effects for the scale in cancer screening or medication decisions. Higher scores associated with less decisional conflict and less decision regret. Retest reliability was acceptable for seven of eight studies.